Outcome of Long-term Maintenance Steroid Therapy Cessation in Patients With Autoimmune Pancreatitis: A Prospective Study. Issue 4 (April 2016) - Hirano, Kenji; Tada, Minoru; Isayama, Hiroyuki; Sasahira, Naoki; Umefune, Gyotane; Akiyama, Dai; Watanabe, Takeo; Saito, Tomotaka; Takagi, Kaoru; Takahara, Naminatsu; Hamada, Tsuyoshi; Mizuno, Suguru; et al.
Abstract : Objective: To predict the duration of steroid maintenance therapy required to achieve good prognosis in patients with autoimmune pancreatitis. Patients and Methods: The study sample comprised 21 patients with autoimmune pancreatitis who met the following criteria: (1) they received steroid therapy (ST) for at least 3 years without clinical relapse; and (2) immunoglobulin (Ig) G<1600 mg/dL was observed in the past year with a prednisolone maintenance dose ⩽5 mg. All patients could be diagnosed with international consensus diagnostic criteria. Patients were prospectively followed up after tapering and cessation of steroids. Clinical relapse was defined as the need to resume ST. Serological relapse was defined as having an IgG level of >1600 mg/dL. Results: During the 43-month (range, 19 to 48 mo) follow-up period, clinical relapse occurred in 10 patients: pancreatic lesion in 4; coronary lesion in 2; submandibular lesion in 1; both pulmonary and renal lesions in 1; pulmonary, retroperitoneal, and submandibular lesions in 1; and bronchial asthma in 1. Serological relapse was observed in 12 patients. Although clinical and serological relapse occurred concomitantly in 3 patients, serological relapse preceded clinical relapse in 4 patients. Five patients experienced serological relapse alone, and no clinical or serological relapse occurred in 6 patients. According to Cox proportional hazard analysis, the duration of ST before tapering was a significant predictive parameter (hazard ratio, 0.969/month; 95% confidence interval, 0.940-0.998; P =0.038). Conclusions: ST cessation resulted in a high rate of clinical relapses, even in patients with long-term maintenance therapy. Therefore, it appears desirable to continue steroid maintenance therapy for a period >3 years to prevent relapse.